Chemical dynamics characteristics of Kapton polyimide damaged by electron beam irradiation. (2nd August 2019) - Rahnamoun, Ali; Engelhart, Daniel P.; Humagain, Sunita; Koerner, Hilmar; Plis, Elena; Kennedy, W. Joshua; Cooper, Russell; Greenbaum, Steven G.; Hoffmann, Ryan; van Duin, Adri C.T.
Abstract: Polyimides, particularly poly-(pyromellitic dianhydride-4, 40-oxydianiline) or PMDA-ODA (Kapton-H ® ), are ubiquitous in the aircraft and aerospace industries, flexible printed circuits, and many other high-performance applications. For many of these applications, the polymer's stability during and after radiation damage is a serious concern. The effect of electron irradiation on the breaking of inter-molecular bonds and creation of free radicals in Kapton polyimide were studied using reactive molecular dynamics simulation with the polarizable ReaxFF method and experimentally on pristine and electron irradiated polyimide by vibrational spectroscopy, electron paramagnetic resonance, nuclear magnetic resonance, wide angle x-ray diffraction, small angle x-ray scattering, and dynamic mechanical analysis. In our simulations, the electron beam is approximated by a dense column of negatively charged particles, which is inserted at random positions in the polyimide matrix. In order to observe inter-molecular bond breaking during the time frame of the molecular simulations, each electron beam is switched on for 2 fs, causing an average energy of 21 eV per electron trajectory to be transferred to the polyimide through Coulomb interactions during the simulation. Experimentally, polyimide is aged in vacuum with a 90 keV electron beam with a maximum penetration depth greater than the material's thickness. Throughout the simulations, modifications in the chemical structure of the polyimide during and after the electron beam irradiations are monitored. During electron beam irradiation, hydrogen atoms separate from different parts of the polyimide through C–H bond cleavage. After turning off the electron beams and running a microcanonical molecular dynamics simulation for 0.5 ns, several chemical and structural rearrangements are observed in the polyimide structure. The chemical modifications mostly include ring opening and other changes to the imide rings. The computations are compared to infrared spectroscopy, electron paramagnetic resonance, nuclear magnetic resonance, x-ray scattering, and mechanical measurements on aged and pristine polyimide to both guide and validate the conclusions from the computational study. Apart from these changes in chemistry we also evaluate temperature evolution and change in mechanical response of the polyimide slab caused by electron beam exposure. Taken together, the direct measurements of the electronic, chemical, and mechanical properties of the irradiated Kapton films validate the key results of the model. Graphical abstract: Image 1 Highlights: Most of the chemical rearrangements are observed in the imide ring spots. Cross linking of the polyimide chains is observed after electron irradiations. Cross linking leads to higher glass transition temperature. Electron beam irradiations cause reduced toughness and increased brittleness.